Autoantibody profiling in intraocular fluid of patients with uveitis. (November 2018) - ten Berge, Josianne C.; Schreurs, Marco WJ.; van Rosmalen, Joost; Rothova, Aniki
Abstract: A high prevalence of serum antiretinal antibodies (ARAs) in patients with uveitis has been previously described, though their clinical role remains elusive. Assessment of intraocular ARAs may provide further insight into the pathogenesis of diverse uveitis entities. In this study we investigate the prevalence of multiple specific anti-ocular antibodies (AOcAs), including ARAs, in intraocular fluid of patients with uveitis. Autoantibody profiling with 188 different ocular antigens was performed by a multiplex immunoassay with intraocular fluid samples of 76 patients with uveitis. Clinical data from uveitis patients were collected and statistical analyses were executed to evaluate associations between intraocular AOcAs and clinical characteristics. Controls consisted of 19 intraocular fluid samples from cataract patients. A spectrum of 22 different AOcAs was present in higher levels in patients with uveitis than in controls (p < 0.05), but in moderately elevated titers (<2x). High elevations of intraocular AOcAs in uveitis (>5x compared to cataract) were observed in varicella zoster virus-induced uveitis, multiple sclerosis-associated uveitis and patients with unexplained uveitis but positive quantiferon test. Presence of macular edema was associated with increased intraocular levels of tyrosinase antibodies. Our results show that patients with uveitis are characterized by the presence of a broad spectrum of moderately elevated levels of intraocular AOcAs, and high intraocular AOcA levels were found in several specific uveitis entities. This study favors secondary production of AOcAs and not their inciting role. Highlights: Uveitis is associated with a broad spectrum of intraocular autoantibodies. Specific uveitis entities exhibit heterogeneous intraocular autoantibody profiles. Macular edema is associated with increased intraocular levels of anti-tyrosinase.